PENGELOLAAN KEBERSIHAN LINGKUNGAN PASAR LUBUK BUAYA KECAMATAN KOTO TANGAH PADANG - Wahyuni, Sri - (STKIP PGRI Sumbar, 2014)
Inin study aims to describe and analyze on Environmental Health Management Market Buaya Lubuk Tangah Koto Padang Subdistrict , in terms of : 1 ) Management of the availability of a place or a means of waste disposal , 2 ) Management of the cleanliness of the place los traders , 3 ) The participation of traders in hygiene bins , 4 ) The governments efforts in the availability of parking.This type of research used in this study is a qualitative analysis of research in the area of market research sites Lubuk Buaya district. Tangah Koto Padang while the information in this study is the office manager of Buaya Lubuk market district. Tangah Koto Padang , and there are 14 merchants using the techniques of documentation , observation , and interview data accuracy is tested by using purposive sampling technique that consists of data reduction and conclusionsThe results showed that: the management of environmental hygiene market Lubuk Buaya district. Tangah Koto Padang is ( 1 ) Management of the availability of a place or a means of waste disposal such as boots , masks and small carts and bins are already available , but the clerk uses these tools are used at a particular time , garbage collection has also been carried out by the janitor market . ( 2 ) Management of the cleanliness of the place los traders have been implemented by the merchant and place it in the wake los government of 1981 as many as 92 plots the store but there are contracted status . ( 3 ) The participation of traders in the cleanliness of garbage just to participate in cleaning up trash alone is by way of cleaning up trash after they sell and they are worn in the payment of hygiene ( parrots ). ( 4 ) The business of government in the management of the parking lot in this market is not really a market agency managers who manage , but which manages the market parking lot to do with parking or transportation agencies called UPTD